United Kingdom : Financial Sector Assessment Program-Systemic Stress, and Climate-Related Financial Risks: Implications for Balance Sheet Resilience. (IMF Staff Country Reports; Country Report, 2022)
The FSAP started in an important macro-financial phase right after the second Covid wave and a third lockdown. The balance sheet resilience of major institutional sectors was at the center of policy considerations. Against this backdrop, the FSAP analyzed the pandemic's potential "scarring" of banks, insurers, corporates, and households balance sheets, focusing on the interplay of macro-financial/structural conditions and financial vulnerabilities.